Age at First Marriage in Recent Years Vietnam - Binh, Nguyen Thanh (Richtmann Publishing, 2012)
In recent years, many studies in Asian countries have shown increased age at first marriage partly due tomodernization (Minh, 2007; Xenos and Gultiano, 1992). Researchers have provided experimental evidences, at both macro andmicro levels, to assert that individuals who possess more modern features (higher education level, more modern professions,and living in urbanized environments) are more likely to get married later than others with less modern features (Smith, 1980;Hirschman, 1985; Smith and Karim, 1980; UNS, 1986). Besides, some other factors can also have a strong impact on thechange in marriage age in Asia such as parents’ interference into children’s marriage or national policies (Minh, 2007). Is it truein present day Vietnam? Based on the results of 2009 Vietnam population and housing census and other surveys, we can affirmthat Vietnamese’s mean age of marriage, especially men’s is rising; for women, this trend has been likely to be stable comparedwith previous decades. Vietnamese men’s mean age at first marriage is higher than women’s in all the periods and regions.Urban young people get married later than rural ones because of the pressure of jobs, income, urban busy life; marriage is notregarded as important as other things. Kinh ethnic group - an ethnic majority in Vietnam, is considered to have moreopportunities to get access to modern life, to know more about national policies so they have a trend to get married later thanethnic minorities. People working in public sector are more likely to get married later than people working in private sector orhouseholds because they suffer pressure from jobs they are in charge of in public sector, as well as seriously obey nationalpolicies related to marriage and family. People at low level of education and doing jobs concerning agriculture before gettingmarried will often get married at younger age.